SBOX: Smart Simple Box - Ahmed Sebaa; BIRANE MOUHOUB (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2024)
This dissertation delves into the SBOX, a groundbreaking device designed to enhance the lives of the elderly and individuals with disabilities through smart home automation. The study covers the Internet of Things (IoT) landscape, highlighting its integration with smart home systems, and detailed insights into the ESP8266, a pivotal component of the SBOX. The research also explores the Android ecosystem, IoT-web development convergence, and photovoltaic systems, culminating in a comprehensive analysis of the SBOX's features, hardware, operational modes, and its role in home energy management. The annex provides an extensive business insight, covering business plans, models, value propositions, market strategies, financial projections, and future growth plans. This work aims to provide a thorough understanding of the SBOX’s technological, economical, and strategic dimensions, positioning it as a revolutionary force in smart home innovation.
Microelectronics